2018
DOI: 10.1158/1541-7786.mcr-17-0655
|View full text |Cite
|
Sign up to set email alerts
|

Methylation of the HOXA10 Promoter Directs miR-196b-5p–Dependent Cell Proliferation and Invasion of Gastric Cancer Cells

Abstract: The cross-talk between epigenetics and miRNA expression plays an important role in human tumorigenesis. Herein, the regulation and role of miR-196b-5p in gastric cancer was investigated. Quantitative real-time RT-PCR (qPCR) demonstrated that miR-196b-5p is significantly overexpressed in human gastric cancer tissues (P<0.01). In addition, it was determined that HOXA10, a homeobox family member and host gene for miR-196b-5p, is overexpressed and positively correlated with miR-196b-5p expression levels (P<0.001).… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 58 publications
(67 reference statements)
4
35
0
Order By: Relevance
“…DNA methylation is reported to lead to gene silencing via inhibiting gene transcription, which has become the most studied epigenetic mechanism [7]. Accumulated studies have showed that aberrant methylation of gene promoter regions is associated with occurrence, progression, and metastasis of several tumors, including ovarian carcinoma [8], gastric cancer [9] and so on. The profile of gene promoter methylation in TGCT was reported by several studies [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…DNA methylation is reported to lead to gene silencing via inhibiting gene transcription, which has become the most studied epigenetic mechanism [7]. Accumulated studies have showed that aberrant methylation of gene promoter regions is associated with occurrence, progression, and metastasis of several tumors, including ovarian carcinoma [8], gastric cancer [9] and so on. The profile of gene promoter methylation in TGCT was reported by several studies [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…MicroRNAs (miRNAs) are a class of small endogenous non-coding genes with~22 nucleotides that exert pivotal roles in post-transcriptional regulation and different biological processes, especially in the progression of cancer [11]. MiR-196b-5p is involved in the progression of several cancers, such as colorectal cancer [12], gastric cancer [13,14]. However, very little is revealed about the role of miR-196b-5p in LC.…”
mentioning
confidence: 99%
“…HOX genes are divided into 4 groups (HOXA, HOXB, HOXC and HOXD) encode transcription factors involved in the control of cell growth (41,42). It has been reported that HOXA10 is associated with cell migration, proliferation and survival in various types of cancer (43,44). In the current study, it was demonstrated that HOXA10 was a direct downstream target of miR-320b through bioinformatic prediction and in vitro experiments, and overexpression of HOXA10 was found to promote the progression and development of NPc cells.…”
Section: Discussionmentioning
confidence: 53%